(untitled) (Albayan Scientific Journal, 2023)
Two Lactobacillus strains (L. acidophilus and L. pentosus) isolated from dairy products, showed good biosurfactant properties. The purpose of this work was to optimize of biosurfactant production by L. acidophilus and L. pentosus and to characterize thesebiosurfactant by FTIR spectroscopy. Maximumbiosurfactant production was achieved when the two isolates grown at pH 7 and 6, incubated at 37 ºC and 36 ºCfor 24 h, 150 rpm and 2% of NaCl respectively. Types of cooking oil as a carbon source and nitrogen source significantly (p<0.05) increased the biosurfactant production. The FTIR analysis showed that biosurfactants from L. acidophilus were composed of a mixture of protein and lipid, while biosurfactants from L. pentosus were composed of a mixture of lipid and carbohydrate,suggesting that the typical structure of biosurfactant were lipopeptides and glycolipids respectively which are affected by medium composition and bacterial growth. The L. acidophilus and L. pentosusare a promising biosurfactant producer which reduced surface tension under a wide range of pH, temperatures, agitation, salinities, time of cultivation, carbon and nitrogen sources and therefore, these strains of Lactobacillus spp. can be added to food formulations to prevent of pathogenic microorganisms growth also they showed a high emulsification index(EI24) values with cooking oil indicating their potential properties as emulsifying agent and could be further exploited for food and pharmaceutical applications.